The Use of Tensor in Lagrangian Coordinates for Motion of Colloidal Particles - Muchammad Chusnan Aprianto (Jurnal Rekayasa Teknologi dan Sains Terapan, 2018)
Colloidal particle is a small size particle with radius between 0.5 to 500 nm. The particle usually floating in a substance such as solid, liquid, and gas. For boundary layer between air – liquid or vice versa, colloidal particle would move on one to another substances i.e. air or liquid in random motion that follow the rules of Brownian motion. The motion could be expressed either in Cartesian or Lagrangian coordinates, but many literatures often expressed in Cartesian coordinates. This article will show the motion of random and colloidal particles in Lagrangian coordinates by using tensor. As the results, for expressing the motion of colloidal particles, the Lagrange coordinates are more simple and general than Cartesian coordinates.